Skill Transferability, Migration, and Development:Evidence from Population Resettlement in Indonesia - Bazzi, Samuel; Gaduh, Arya; Rothenberg, Alexander D.; Wong, Maisy (American Economic Review, 2016)
We use a natural experiment in Indonesia to provide causal evidence on the role of location-specific human capital and skill transferability in shaping the spatial distribution of productivity. From 1979–1988, the Transmigration Program relocated two million migrants from rural Java and Bali to new rural settlements in the Outer Islands. Villages assigned migrants from regions with more similar agroclimatic endowments exhibit higher rice productivity and nighttime light intensity one to two decades later. We find some evidence of migrants' adaptation to agroclimatic change. Overall, our results suggest that regional productivity differences may overstate the potential gains from migration. (JEL J24, J43, J61, O13, O15, Q13, R23)